Analisis Mendalam Mengenai Implementasi Sistem Informasi Dalam Rangka Pemberdayaan Dan Peningkatan Kesejahteraan Keluarga Di Lingkup Pkk Provinsi Lampung - Rauf, Eka Ubaya Taruna; Wisnaningsih, Wisnaningsih; Juwita, Farida; Suri, Intan (e-JKPP, 2024)
The province of Lampung implements the Family Empowerment and Welfare Information System (SIPPK). The management of this system is based on the work programs of the PKK Mobilizing Team, aimed at facilitating online services for the team and emphasizing the importance of family empowerment and welfare programs. However, it is observed that the cadres face challenges due to inadequate equipment, limited work facilities, and unappealing communication methods, which hinder the implementation of family empowerment and welfare programs. This affects the cadres' performance in carrying out the PKK programs optimally. When the information system is not well implemented, the cadres struggle to identify or plan programs that meet community needs. They also face difficulties in gathering, mobilizing, and nurturing community potential, particularly families, leading to less effective implementation of PKK programs. This study aims to understand the implementation of the Family Empowerment and Welfare Information System and assess the performance of PKK cadres in Lampung province. Data was collected through observations, interviews, and documentation, and analyzed qualitatively. The results show that the implementation of the information system in Lampung faces challenges, such as the lack of supporting devices like laptops or projectors, which hinders effective communication and socialization. This leads to monotonous, less engaging communication and affects the cadres' performance in executing the Family Empowerment and Welfare Information System.